Pengaruh Implementasi Manajemen Kelas Terhadap Hasil Belajar Peserta Didik di SMK Muhammadiyah Watansoppeng - A Sri Reski Amaliah; Muhammad Yahya; Ahmad Afiif (Institut Agama Islam Negeri (IAIN) Palopo, 2019)
This research aimed to find the implementation and effect of classroom management on learning outcome of students. It is a field research with a quantitative approach, using descriptive quantitative statistic analysis as an analylis data technique. The results of the data found about the significance of classroom management on student learning outcomes at SMK Muhammadiyah Watansoppeng.